Comparasion of Sport Urine Protein Creatinine From Three Different Time Urine Samples in Children With Primary Nephrotic - Jusuf Hartanto Mohammad Juffrie Pungky Ardani (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: First voiding of morning urine protein/creatinine ratio on a single voided urine sample correlates well with 24 hour urine collection and can be used to detect and monitor proteinuria in children. Objective: Aim of this study was to determine whether the random urine samples can be used as reliable indicator for spot urine protein/creatinine ratio.Methods: 40 primary nephrotic syndrome children aged 1-16 years admitted to the Department of Pediatric, Dr Sardjito hospital were included in this study. Urine samples from three different times were collected: first voiding of morning urine, noon voiding and night voiding. The three samples were analyzed for protein level, creatinine level and protein/creatinine ratio of spot urine. The protein/creatinine ratio was compared and correlation was calculated according to the three different time collections.Results: There was no significant difference of noon and night protein/creatinine ratio compared with first voiding of morning urine protein creatinine ratio (p> 0.05). The correlation of protein/creatinine ratio between the three samples was significantly high (r=0.95, 0.96 and 0.98, p < 0.01).Conclusions: For quantifying proteinuria, there is convincing evidence that the random urine samples can be used to predict the level of protein excretion as measured in a 24-hour sample.Keywords: Proteinuria, protein, creatinine ratio, primary nephrotic syndrome